2013
DOI: 10.1037/a0030541
|View full text |Cite
|
Sign up to set email alerts
|

Demands, control, and support: A meta-analytic review of work characteristics interrelationships.

Abstract: The job demands-control-support model (DCS; Karasek, 1979) is an influential theory for understanding how work characteristics relate to employee well-being, health, and performance. However, previous research has largely neglected theory-building regarding the interrelationships between job demands, control, and support. We remedy such theoretical underdevelopment by reviewing and integrating theory on the relationships between demands, control, and support to develop five hypotheses. We test our hypotheses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
157
1
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(176 citation statements)
references
References 189 publications
(149 reference statements)
9
157
1
9
Order By: Relevance
“…None of the tested JDCS interaction effects were significant predicators within the given sample of teachers. Previous studies have observed consistent evidence of the main effects of the JDCS work characteristics (Noblet and LaMontagne 2006;Hausser et al, 2010;Luchman and Gonzales-Morales, 2013); however, evidence of their interactive nature of these variables is mixed and observably weak (van der Doef and Maes, 1999;De Lange et al, 2003).…”
Section: The Influence Of Jdcs Work Characteristicsmentioning
confidence: 87%
“…None of the tested JDCS interaction effects were significant predicators within the given sample of teachers. Previous studies have observed consistent evidence of the main effects of the JDCS work characteristics (Noblet and LaMontagne 2006;Hausser et al, 2010;Luchman and Gonzales-Morales, 2013); however, evidence of their interactive nature of these variables is mixed and observably weak (van der Doef and Maes, 1999;De Lange et al, 2003).…”
Section: The Influence Of Jdcs Work Characteristicsmentioning
confidence: 87%
“…Such work designs are associated with, for example: better physical well-being, including physical fitness (Fransson et al, 2012), lower hypertension (Babu et al, 2014), fewer headaches/ gastrointestinal problems (Nixon, Mazzola, Bauer, Krueger, & Spector, 2011) and lowered incidence of musculoskeletal disorders (Eijckelhof et al, 2013); higher mental health and psychological well-being (Luchman & González-Morales, 2013); more positive job attitudes, such as job satisfaction and organizational commitment (Humphrey et al, 2007); better job performance (Humphrey et al, 2007); and higher levels of innovation (Hammond, Neff, Farr, Schwall, & Zhao, 2011). Studies also show positive effects at higher levels in the organization, such as group work design enhancing team effectiveness (Campion, Papper, & Medsker, 1996;Xanthopoulou, Bakker, Demerouti, & Schaufeli, 2009) and team innovation (Hülsheger, Anderson, & Salgado, 2009).…”
Section: Mainstream Research: How Work Design Affects Outcomesmentioning
confidence: 99%
“…The Job Demand-Control model developed by Karasek (1979) is a leading model for studying the effect of job characteristics on employee well-being, health and performance (Luchman & Gloria, 2013). Depending on the levels of job demands and control experienced by the employee, workers will have different outcomes in terms of job strain and active learning.…”
Section: Literature the Karasek Model And The Learning Hypothesismentioning
confidence: 99%